The Role of Electronic Accounting in Reducing Audit Risks (Field study on some auditing offices in Khartoum state, 2022) - Mustafa, AbdElazim AbdElrahman Elbashir (Journal of Economic, Administrative and Legal Sciences, 2022)
This study mainly aimed to know the role played by electronic accounting in reducing audit risks, by identifying the extent to which electronic accounting is used in the Sudanese business environment. The study found several results, among which is that, (56) individuals, who represented (93) of the study sample agreed that, the use of electronic applications in the field of financial and governmental accounting reduces the risk of audit control, and (57) individuals who represented (95%) of the study sample agreed that, the accuracy and speed of entering financial data provided by electronic accounting contribute to reducing the risks of discovery in the audit. The study concluded with several recommendations, the most important of which is increasing awareness of the various audit risks in the Sudanese business environment, especially in light of the electronic operation of data, through workshops and seminars.